East–West differences in clinical manifestations of COVID‐19 patients: A systematic literature review and meta‐analysis. Issue 5 (23rd February 2021) - Liu, Xiucheng; Li, Xiang; Sun, Teng; Qin, Hao; Zhou, Yeqing; Zou, Chenghang; Cao, Junli; Zhang, Hao
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic is currently not under control. We aimed to assess whether there are differences in clinical manifestations between COVID‐19 patients from the East (East and South‐East Asian countries including China, South Korea, and Thailand) and the West (North American, European, and Middle East countries, including the United States, Italy, France, and Iran). For this meta‐analysis, we searched for eligible studies about COVID‐19 in three databases: PubMed, EMBASE, and the Cochrane Library. Studies were divided into two cohorts for analysis: the East and the West. Stata 13.1 software was used for the meta‐analysis. Of the 1527 studies initially identified by the literature search, 169 full‐text articles were retrieved and screened for eligibility. Fifty‐seven of these, describing 19, 353 patients, were deemed eligible for inclusion. Of these, 45 studies with 8416 patients were from the East while 12 studies with 10, 937 patients were from the West. The results indicated that the incidences of cough, headache, dizziness, nasal congestion, and digestive symptoms in COVID‐19 patients from the East were lower than those in the West. The laboratory data showed that there were no significant differences in the levels of lymphocytes, leukocytes, C‐reactive protein, and platelet counts between the two groups. In addition, our results also showed that the incidence of cardiac and kidney injury, as well as increased levels of creatinine, alanine transaminase, and aspartate transaminase, were significantly higher in patients from the West than from the East. Our meta‐analysis indicated that there are differences in the clinical manifestations of COVID‐19 in patients from the East and the West. COVID‐19 patients from the West appear to suffer more severe liver, kidney, and heart damage due to SARS‐CoV‐2.